The Role of School Principals in Improving Teacher Performance Through the Merdeka Mengajar Platform - Kustomo Kustomo (Digital Innovation : International Journal of Management, 2025)
This study aims to explore the role of school principals in enhancing teacher performance through the utilization of the Platform Merdeka Mengajar, a digital tool introduced by the Indonesian Ministry of Education and Culture to improve the quality of teaching and learning. The research was conducted at SMP N 4 Jombang, employing a qualitative approach with a case study design to gain an in-depth understanding of how principals support teachers in using this platform effectively. Data were collected through interviews with principals and teachers, as well as classroom observations. The findings indicate that the principal’s leadership, underpinned by managerial competencies such as planning, organizing, supervising, and human resource development, plays a critical role in facilitating the integration of technology into teaching practices. Principals provided technical support, organized training sessions, motivated teachers, and created a collaborative environment to enhance the use of the platform. Additionally, the study found that the Platform Merdeka Mengajar positively impacted teacher creativity and the quality of learning interactions. However, the study also highlights challenges, such as limited technological infrastructure and the varying levels of digital literacy among teachers. The results underscore the importance of strong leadership in educational technology implementation and offer insights into effective strategies for enhancing teacher performance through digital platforms. The study also identifies limitations related to its sample size and scope and suggests avenues for future research on long-term impacts and the role of external factors in educational technology adoption.